Incidence of Type 1 Diabetes in Children Aged Below 18 Years during 2013-2015 in Northwest Turkey - BEREKET, ABDULLAH; DEMİRCİOĞLU, SERAP; GÜRAN, TÜLAY (GALENOS YAYINCILIK, 2018)
Objective: To assess the incidence of type I diabetes mellitus (T1DM) in children under 18 years of age in the northwest region of Turkey during 2013-2015. Methods: All newly diagnosed T1DM cases were recorded prospectively during 2013-2015. Total, as well as gender and age group specific (0-4, 5-9. 10-14 and 15-17 age) mean incidences per 100,000 per year were calculated. Results: There were 1,773 patients diagnosed during 2013-2015 (588 cases in 2013, 592 cases in 2014, 593 cases in 2015). Of these, 862 (48.6 %) were girls and 911 (51.4%)were boys. The mean age at diagnosis was 9.2 +/- 4.2 years and it was not significantly different between girls (9.0 +/- 4.1 years) and boys (9.4 +/- 4.4 years) (p = 0.052). The crude mean incidence was 8.99/100.000 confidence interval (CI) (95% CI: 8.58-9.42). Although mean incidence was similar between boys [8.98/100.000 (CI: 8.40 to 9.58)] and girls [9.01/100.000 (CI: 8.42 to 9.63)], there was male predominance in all groups except for 5-9 year age group. The standardized mean incidence was 9.02/100.000 according to the World Health Organization standard population. The mean incidence for the 0-4, 5-9, 10-14 and 15-17 age groups was 6.13, 11.68, 11.7 and 5.04/1 00.000 respectively. The incidence of T1DM was similar over the course of three years (p = 0.95). A significant increase in the proportion of cases diagnosed was observed in the autumn-winter seasons. Conclusion: The northwest region of Turkey experienced an intermediate incidence of T1DM over the period of the study.
Keywords: Type 1 diabetes mellitus; childhood; incidence; RAPIDLY RISING INCIDENCE; SEASONAL-VARIATION; NATIONWIDE INCIDENCE; MELLITUS; ONSET; PREVALENCE; TRENDS; TIME; EPIDEMIOLOGY; DIAGNOSIS